0
$\begingroup$

Let $f$ be analytic at $z_0\in\Bbb{C}$ and $g$ have a simple pole at $z_0$. Find $\operatorname{Res}(f(g(z_0)),z_0)$.

scratchwork (Would like big hints. I don't usually like asking for the full answer, but I have no choice this time.):

If $g$ has a simple pole at $z_0$ with residue $A$, then \begin{align} \operatorname{Res}(g(z),z_0)=\lim_{z\to z_0}(z-z_0)g(z)=\lim_{z\to z_0}(z-z_0)\frac{h(z)}{z-z_0}=\lim_{z\to z_0}h(z)=A \quad \text{, for some function h(z).} \end{align} Since $f$ is analytic at $z_0\in\Bbb{C}$, then it has taylor series representation, say $f(z)=\sum_{k=0}^\infty \frac{f^{(k)}(z_0)}{k!}(z-z_0)^k$.

Original problem statement(verbatim): Let $f$ be analytic at $z=z_0$. calculate $\operatorname{Res}(fg,z_0)$, if

  • (a) $g$ has a simple pole with residue $A$ at z=z_0.
  • (b) $g$ has a pole of order $k$ and principal part given by

\begin{align} \frac{a_{-1}}{z-z_0}+\frac{a_{-2}}{(z-z_0)^2}+\cdots +\frac{a_{-k}}{(z-z_0)^k} \end{align}

$\endgroup$
  • 2
    $\begingroup$ There is something wrong with the way the question is stated. The fact that $f$ is analytic at $z_0$ is of no use because we are interested in $f(g(z))$ for $z$ neat $z_0$. $\endgroup$ – Kabo Murphy Oct 26 '18 at 9:52
  • $\begingroup$ Hold on. I'll upload a picture. thank you guys! $\endgroup$ – TheLast Cipher Oct 26 '18 at 9:54
  • $\begingroup$ Don't upload a picture! Use MathJax. $\endgroup$ – José Carlos Santos Oct 26 '18 at 9:56
  • 2
    $\begingroup$ You are reading the product $fg$ as $f\circ g$. @TheLastCipher $\endgroup$ – Kabo Murphy Oct 26 '18 at 9:58
  • 1
    $\begingroup$ As stated it is the product of functions not the composite function. $\endgroup$ – Shashi Oct 26 '18 at 9:58
1
$\begingroup$

The answer is $f(z_0)\operatorname{res}\bigl(g(z),z_0\bigr)$, since$$\lim_{z\to z_0}(z-z_0)f(z)g(z)=\lim_{z\to z_0}f(z)\times\lim_{z\to z_0}(z-z_0)g(z)=f(z_0)\operatorname{res}\bigl(g(z),z_0\bigr).$$


For the second part. note that if$$f(z)=a_0+a_1(z-z_0)+a_2(z-z_0)^2+\cdots$$and$$g(z)=\frac{b_{-k}}{(z-z_0)^k}+\frac{b_{-k+1}}{(z-z_0)^{k-1}}+\cdots=\frac1{(z-z_0)^k}\left(b_{-k}+b_{-k+1}(z-z_0)+\cdots\right),$$then $(z-z_0)^{k-1}$ in$$\left(a_0+a_1(z-z_0)+a_2(z-z_0)^2+\cdots\right)\times\left(b_{-k}+b_{-k+1}(z-z_0)+\cdots\right),$$which is $a_0b_{-1}+a_1b_{-2}+\cdots+a_{k-1}b_{-k}$.

$\endgroup$
  • $\begingroup$ I agree. thanks!! $\endgroup$ – TheLast Cipher Oct 26 '18 at 10:06
  • $\begingroup$ As for part (b), I am stuck with $\operatorname{Res}(fg,z_0)=\frac{1}{(k-1)!}\lim_{z \to z_0}\frac{d^{k-1}}{dz^{k-1}}[(z-z_0)^{k}fg]=\frac{1}{(k-1)!}\lim_{z\to z_0}\frac{d^{k-1}}{dz^{k-1}}[f(z)h(z)]$ such that $g(z)=h(z)/(z-z_0)^k$ and the fact that $\frac{d^{k-1}}{dz^{k-1}}[h(z)]=(k-1)!a_{-1}+\cdots$. $\endgroup$ – TheLast Cipher Oct 26 '18 at 10:51
  • 1
    $\begingroup$ I've edited my answer. $\endgroup$ – José Carlos Santos Oct 26 '18 at 11:02
  • $\begingroup$ Wow. How did you deduce the coefficient so quickly by simple expansion? $\endgroup$ – TheLast Cipher Oct 26 '18 at 11:09
  • 1
    $\begingroup$ I computed the product. It's like multiplying polynomials. $\endgroup$ – José Carlos Santos Oct 26 '18 at 11:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.